Sejarah dan Perkembangan Kesenian Wayang Gantung di Kota Singkawang - Haris Firmansyah; Astrini Eka Putri (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
The purpose of this study is to find out how the history and development of the hanging puppet tradition in Singkawang City. This research is basic research. Qualitative data collected mainly in the form of words. To answer how the history and development of the hanging puppet art in Singkawang City, the informants who will be used as resource persons are Singkawang local traditional arts figures. In addition, it also utilizes the literature or the results of previous research. This interactive analysis technique has three components of analysis, namely data reduction, data presentation and drawing conclusions or verification. The result of this research is that the Hanging Puppet in Singkawang City became known in the early 20th century. The character who first introduced the wayang hang art in Singkawang City was Ajo or A Jong. The Chinese community in Singkawang City usually knows the hanging wayang with the term Chiao thew hi which comes from the Hakka language (Khek). The love of the people of Singkawang City for the art of wayang hanging began to increase rapidly in the 1960s. The large number of associations or groups of wayang hang artists in Singkawang City is one of the characteristics of the golden age of wayang hanging.